Low‐pressure plasma activation enables enhanced adipose‐derived stem cell adhesion. Issue 4 (17th October 2019) - Kleinhans, Claudia; Schmohl, Lena; Barz, Jakob; Kluger, Petra J.
Abstract: Human adipose‐derived stem cells (hASCs) have become an important cell source for the use in tissue engineering and other medical applications. Not every biomaterial is suitable for human cell culture and requires surface modifications to enable cell adhesion and proliferation. Our hypothesis is that chemical surface modifications introduced by low‐discharge plasma enhance the adhesion and proliferation of hASCs. Polystyrene (PS) surfaces were modified either by ammonia (NH3 ), carbon dioxide (CO2 ) or acrylic acid (AAc) plasma. The results show that the initial cell adhesion is significantly higher on all modified surfaces than on unmodified material as evaluated by bright field microscopy, live/dead staining, total DNA amount and scanning electron microscopy. The formation of focal adhesions was well pronounced on the Tissue Culture PS, NH3 ‐, and CO2 ‐plasma modified samples. The number of matured fibrillar adhesions was significantly higher on NH3 ‐plasma modified surfaces than on all other surfaces. Our study validates the suitability of chemical plasma activation and represents a method to enhance hASCs adhesion and improved cell expansion. All chemical modification promoted hASCs adhesion and can therefore be used for the modification of different scaffold materials whereby NH3 ‐plasma modified surfaces resulted in the best outcome concerning hASCs adhesion and proliferation.